Effects of postharvest collision damage on qualities of kiwifruit during storage - He, Ke; Qiao, Mengmeng; Liu, Wenzheng; Sun, Xiangyu; Fang, Yulin; Su, Yuan (Frontiers in Plant Science, 2025)
IntroductionUnderstanding the physicochemical quality variations of kiwifruit subjected to repeated collisions during storage is critical for optimizing postharvest processing and improving handling equipment. However, this issue has received limited research attention. This study investigated the effects of different factors (storage time, collision position, and collision frequency) on the quality of kiwifruit during storage. This study provides new insights into the preservation and storage of kiwifruit.MethodsIn this study, the effects of three collision frequencies (1, 3, and 5 impacts), three collision positions (top/stem shoulder, middle/cheek, and bottom/calyx shoulder) simulated using an impactor, and a storage period of 42 days were evaluated on the physicochemical properties of kiwifruit. Multivariate analysis of variance was performed on weight loss rate (WL), hardness, soluble solids content (SSC), titratable acidity (TA), reducing sugars (RS), and vitamin C (VC).ResultsThe results showed that these factors significantly influenced WL and the hardness of kiwifruit. The collision frequency and collision position both affected SSC and RS, whereas collision frequency significantly influenced VC content but not TA. On the contrary, the collision position had no significant effect on VC content but significantly affected TA. The coefficient of determination R2 for all multiple regression models exceeded 0.5. Furthermore, correlation analysis demonstrated that repeated collisions accelerated kiwifruit ripening, and weakened the correlation among physicochemical properties.DiscussionOverall, this study highlights the substantial impact of mechanical damage on the physicochemical quality attributes of kiwifruit during storage, offering a new perspective for assessing damage sensitivity under different storage conditions.